PRESENTASI DIRI MAHASISWA PADA AKUN INSTAGRAM (Analisis Mahasiswa Fisip Unri Yang Memiliki Dua Akun Instagram) - Cindi Septia; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Instagram is a popuIar sociaI media appIication among people of all ages, including students. Instagram social media has raised important issues related to freedom of expression. Another interesting phenomenon to study regarding Instagram is how its users interact and treat their accounts differently. This study aims to find out how the five students presented themselves on the front stage and back stage from the first account and the second Instagram account using Ervin Goffman's Dramaturgy theory. The author uses qualitative research methods and uses purposive sampling technique. Instrument data are observation, interviews, and documentation. The results of this study can be concIuded that the reason why students use account two is to minimize their followers on the first account so that they use two special followers accounts that are allowed by the account owner.                                                                                                                         Keywords : Self Presentation, Instagram, Two Accounts, Student